2016
DOI: 10.1093/mnras/stv2945
|View full text |Cite
|
Sign up to set email alerts
|

A variable ULX and possible IMBH candidate in M51a

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 82 publications
8
51
0
Order By: Relevance
“…The presence of IMBHs was also suggested in the HLXs 2XMM J011942.7+032421 (Sutton et al 2012;Gutiérrez & Moon 2014) and CXO J122518.6+144545 (Jonker et al 2010;Heida et al 2015), and in the ULXs NGC 1313 X-1 (e.g., Pasham et al 2015), NGC 5408 X-1 (e.g., Dheeraj & Strohmayer 2012), and M51 ULX-7 (Earnshaw et al 2016), among others. The HLX 2XMM J011942.7+032421, with a peak X-ray luminosity of 1.53 ×10 41 erg s −1 , presents short-term variability and its X-ray spectrum can be fitted by multicolor disk emission with a mass ≥ 1900 M (Sutton et al 2012).…”
Section: Ultraluminous X-ray Sourcesmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of IMBHs was also suggested in the HLXs 2XMM J011942.7+032421 (Sutton et al 2012;Gutiérrez & Moon 2014) and CXO J122518.6+144545 (Jonker et al 2010;Heida et al 2015), and in the ULXs NGC 1313 X-1 (e.g., Pasham et al 2015), NGC 5408 X-1 (e.g., Dheeraj & Strohmayer 2012), and M51 ULX-7 (Earnshaw et al 2016), among others. The HLX 2XMM J011942.7+032421, with a peak X-ray luminosity of 1.53 ×10 41 erg s −1 , presents short-term variability and its X-ray spectrum can be fitted by multicolor disk emission with a mass ≥ 1900 M (Sutton et al 2012).…”
Section: Ultraluminous X-ray Sourcesmentioning
confidence: 90%
“…The recent detection of an ultra-fast outflow in the X-ray spectrum of NGC 5408 X-1 finally confirmed the super-Eddington accreting nature of this source ). Last but not least, the ULX-7 in the spiral galaxy M51 is suggested to be powered by an IMBH based on its hard spectrum, high rms variability, and the lower limit on the BH mass of 1.6 × 10 3 M derived using the relationship between BH mass and high frequency break in the power spectrum (Earnshaw et al 2016). However, a pulsar nature for this ULX cannot be ruled out.…”
Section: Ultraluminous X-ray Sourcesmentioning
confidence: 99%
“…The class of ultraluminous X-ray sources (ULX) have Lx ∼ 10 39 − 10 42 erg s −1 (Swartz et al 2004), and it is thought that some of these are powered by pulsars, stellarmass black holes, and possibly intermediate-mass black holes for the most luminous of them (Mezcua et al 2013;Earnshaw et al 2016;Mezcua et al 2016;Bachetti 2016). The pulsars and stellar-mass black holes are associated with highmass star formation, and hence with molecular clouds.…”
Section: Discussionmentioning
confidence: 99%
“…Pasham et al, 2014;Wrobel et al, 2016;Earnshaw et al, 2016;Arca-Sedda, 2016). Kiziltan et al (2017) found an indirect evidence for an IMBH of about 2200 M ⊙ at the center of the globular cluster 47 Tucanae based on the dynamical state constrained by the timing data of millisecond pulsars.…”
Section: Working Definition Of a (Supermassive) Black Holementioning
confidence: 99%